Physiological Changes in Serum Calcium, Phosphate, Vitamin D, Parathyroid Hormone and Calcitonin During Pregnancy and Lactation in Randomised Population of Zaria Women (Nigerian Journal of Physiological Sciences, 2022)
Pregnancy and lactation are usual but stressful physiological conditions accompanied by changes in calcium and phosphate metabolism and their regulatory hormones which may lead to calcium-related disorders in pregnant women. This study aimed to evaluate the changes in serum levels of calcium, phosphate, vitamin D and their regulatory hormones in pregnant and lactating women in Zaria, Nigeria. A cross‑sectional descriptive study was conducted at Ahmadu Bello University Teaching Hospital, Zaria for three (3) months. Blood samples were collected, anthropometric measurements (weight, height and body mass index) of 179 women were taken. Serum calcium, phosphate, vitamin D, parathyroid hormone and calcitonin were determined using standard methods. Data were presented as mean ± SD, analysis was performed using one-way ANOVA and Pearson’s correlation analysis. Values were considered significant at p ≤ 0.05. There was a significant decrease in serum calcium concentration (p < 0.01) during the third trimester of pregnancy and lactation. An increase in serum concentration of vitamin D, parathyroid hormone, and calcitonin in the 2nd trimester and a decrease during the third trimester and lactation although not statistically significant when compared with the control. There was a negative correlation between serum calcium concentration and gestational age (r = 0.255) while no correlation between gestational age and serum phosphate concentration. Changes in serum calcium, vitamin D, parathyroid hormone and calcitonin during pregnancy and lactation has been demonstrated suggesting a relationship between calcium metabolism and these hormones at some stages of pregnancy